Comparison between Gutta-Percha and Resin-Coated Gutta-Percha using Different Obturation Techniques. Issue 3 (July 2016) - Al-Afifi, Nashwan A.; Abdullah, Mariam; Al-Amery, Samah M.; Abdulmunem, Mohamed
Background: The aim of this study was to evaluate and compare the obturation quality between canals obturated with gutta-percha/AH Plus sealer (GP group) and resin-coated GP/EndoREZ® sealer (ER group). Methods: A total sample of 90 mandibular premolar teeth was divided into 2 groups (2 × 45 canals): the GP group and ER group. Each group was further divided into 3 subgroups (n = 15): cold lateral compaction (CLC), warm lateral compaction (WLC) and single cone (SC). The teeth were subsequently embedded in resin and sectioned horizontally at 1, 3, 6 and 9 mm. All sections were then viewed with a stereomicroscope at ×40 magnification. The area occupied by core filling materials was determined using Cell^D software. Results: With CLC, the percentage of core filling materials in the ER group was significantly higher than in the GP group at the 1- and 3-mm levels. Similarly, with WLC, the percentage of core filling material in the ER group was significantly higher than in the GP group at the 1-, 3- and 9-mm levels. With SC, the percentage of core filling materials in the ER group was significantly higher than in the GP group at all levels. Conclusions: It can be concluded that the resin-coated GP/EndoREZ® sealer is superior to the gutta-percha/AH Plus in the percentage of core filling material.